Internalized-stigma and dissociative experiences in bipolar disorder - de Filippis, Renato; Menculini, Giulia; D'Angelo, Martina; Carbone, Elvira Anna; Tortorella, Alfonso; De Fazio, Pasquale; Steardo, Luca (Frontiers in Psychiatry, 2022)
Introduction Dissociative symptoms have been recently related to bipolar disorder (BD) symptomatology. Moreover, the disease burden carries on a share of perceived self-stigma that amplifies the BD impairment. Internalized stigma and dissociative symptoms often seem overlapping, leading toward common outcomes, with reduced treatment seeking and poor adherence. We hypothesize a potential relationship between dissociation and self-stigma in patients suffering from BD. Materials and methods In this cross-sectional study we enrolled a total of 120 adult clinically stable BD outpatients. All participants completed the Internalized Stigma of Mental Illness (ISMI), Dissociative Experiences Scale-II (DES-II), and Manchester Short Assessment of Quality of Life (MANSA). Results Average age and age at BD (BD-I n = 66, 55%; BD-II n = 54, 45%) onset were 46.14 (±4.23), and 27.45 (±10.35) years, with mean disease duration of 18.56 (±13.08) years. Most participants were female (n = 71; 59.2%) and 40 (33%) of them experienced lifetime abuse, with an average of 1.05 (±0.78) suicide attempts. DES scores (mean 31.8, ±21.6) correlated with ISMI total-score, with significant association with spikes in Alienation (13.1, SD±3.1) (p < 0.001) and Stereotype (13.8, SD±3.9) (p < 0.001). Linear regression analysis has shown a significant association between DES total score and alienation (p < 0.001), stereotype (p < 0.001) and MANSA total-score (p < 0.001). Discussion For the first time, our data suggests that self-stigma is associated to dissociative symptoms, reducing overall quality of life in BD. The early identification of at-risk patients with previous lifetime abuse and high perceived stigma could lead the way for an ever more precise tailoring of treatment management.